The Effect of Smartphone Addiction on Students' Academic Proscrastination - Putri Anjani Simbolon; Nurussakinah Daulay (Jurnal Basicedu, 2022)
The use of smartphones is a primary need in accessing information on learning resources in the era of the Covid-19 pandemic. Through smartphones, work and various educational processes are made easy, because they can connect communication remotely. Likewise, smartphones when used excessively can cause problems in the student learning process, including procrastination or academic procrastination. This study aims to determine whether smartphone addiction has an effect on academic procrastination behavior in students. The method used is quantitative research, with a total number of research subjects, namely 172 students. The sampling technique is cluster random sampling. The data collection method used a smartphone addiction scale and a procrastination scale. The results of this study indicate that there is an effect of smartphone addiction on students' academic procrastination with the details of the value of t = -3.177 and p = 0.002 <0.05.